Pedagogies of Praxis: Exercises in Embodying Social Justice for Performance Studies Seminars - Erincin, Serap (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2023)
This article discusses my pedagogies of praxis in the performance studies classroom focused on identity, inclusion, and social justice. I especially consider methodologies I employ in seminars focused on analyzing and making social justice performances such as Performing Human Rights and Performing Activism. This discussion explores the significance of embodied ways of learning and the materialities of the performance studies classroom. I argue that such praxis—which combines foundational and cutting-edge theories in the field, analysis of sites of performance that exemplify such work, and affective exercises that allow students to embody these theories through their lived experience—creates the most meaningful learning outcomes. I discuss various exercises I developed which offer up a material trace of the embodied, praxis-oriented pedagogy that I centre in my seminars focused on analyzing and making social justice performances.